(untitled) (Academia Science Repository, 2023)
At present, the scale of teaching foreign languages in schools and universities is actively increasing. In connection with this, new ar eas of training are opening up, new curricula are being developed, and new disciplines are being developed. In the modern world, the study of foreign languages has become a requirement as we find ourselves involved in two, three, or more cultures at the sa me time. Various life circumstances contribute to the emergence of such situations: long business trips, interethnic marriages, educational programs, immigration, as well as living in multilingual and multicultural regions. Knowledge of foreign languages h as become necessary, as in connection with the expansion of relations between other countries, it has become necessary to speak at least one foreign language. Representatives of many professions, in addition to their specialty, must know a foreign language in order to be able to find a common language with foreigners.